2019
DOI: 10.1186/s12913-019-4846-y
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of healthcare services among Chinese migrants in Kenya: a qualitative study

Abstract: BackgroundThe number of Chinese migrants in Sub-Saharan Africa (SSA) is increasing, which is part of the south-south migration. The healthcare seeking challenges for Chinese migrants in Africa are different from local people and other global migrants. The aim of this study is to explore utilization of local health services and barriers to health services access among Chinese migrants in Kenya.MethodsThirteen in-depth interviews (IDIs) and six focus group discussions (FGDs) were conducted among Chinese migrants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…We speak Arabic." (Gericke et al, 2018) Excessive/slow bureaucratization (fear for deportation) (Brandenberger et al, 2019;Daftary, 2020;Ferrer-Wreder et al, 2020;Gericke et al, 2018;Houston et al, 2021;Kaufmann, 2018;Knaifel, 2021;Larson et al, 2017;Loganathan et al, 2019;Luque et al, 2018;Mangrio et al, 2019;Mullings et al, 2020;Murillo-Pedrozo et al, 2021;Nielsen et al, 2017;Orozco Vargas, 2018 and duties of citizens (Bhandari et al, 2021;Chu et al, 2015;Cicognani et al, 2018;Mangrio et al, 2019;Mullings et al, 2020;Orozco Vargas, 2018;Pérez-Urdiales et al, 2019;…”
Section: Uncertainty and Health Implicationsmentioning
confidence: 99%
“…We speak Arabic." (Gericke et al, 2018) Excessive/slow bureaucratization (fear for deportation) (Brandenberger et al, 2019;Daftary, 2020;Ferrer-Wreder et al, 2020;Gericke et al, 2018;Houston et al, 2021;Kaufmann, 2018;Knaifel, 2021;Larson et al, 2017;Loganathan et al, 2019;Luque et al, 2018;Mangrio et al, 2019;Mullings et al, 2020;Murillo-Pedrozo et al, 2021;Nielsen et al, 2017;Orozco Vargas, 2018 and duties of citizens (Bhandari et al, 2021;Chu et al, 2015;Cicognani et al, 2018;Mangrio et al, 2019;Mullings et al, 2020;Orozco Vargas, 2018;Pérez-Urdiales et al, 2019;…”
Section: Uncertainty and Health Implicationsmentioning
confidence: 99%
“…However, minimal research on IMs found financial constraints (12), and major financial sources (38) are irrelevant because they do not directly determine the purchasing capacity for healthcare services. Second, since participation in any medical insurance program could effectively reduce the medical burden, medical insurance (13,95,129) is another important aspect of financial resources associated with migrants' HSU and whether insurance is associated with immigrants' (77,82,88,(130)(131)(132) and IMs' (11,12,50,57,72,78,92,100,127,128,133) HSU. Immigrants' HSU is associated with paying the medical insurance premium regularly (114), which was associated with the availability of medical insurance.…”
Section: Enabling Resourcesmentioning
confidence: 99%
“…Acculturation is mentioned as a protective factor in the overwhelming majority of studies on immigrants' HSU (138). These studies explain acculturation by language competence (40,41,43,44,46,60,62,64,65,69,76,77,79,97,114,120,124,139,140) or communication barriers (3,117,121), discrimination or xenophobia (3,42,43,60,65,71,120), cultural differences (62,75,76,79,89,117,121,124), and self-identified (89). All factors induce poor affective comfort during the HSU process.…”
Section: Immigrant-specific Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…International studies indicate that Chinese immigrants seek health services on a smaller scale than other immigrant communities [7,9]. The use of TCM [18][19][20][21], self-medication [22], the search for healthcare in China [10,23], the language barrier and the time spent [24] could be factors that explain the behaviour of these immigrants [25].…”
Section: Introductionmentioning
confidence: 99%